DEVELOPMENT OF MIND MAPPING-BASED ELECTRONIC MODULES (E-MODULES) IN THE SUBJECT OF PANCASILA EDUCATION ON THE MATERIAL OF GOTONG ROYONG FOR GRADE IV OF MLATIHARJO 2 ELEMENTARY SCHOOL - Ryan Prayogo; Wawan Shokib Rondli; Nur Fajrie (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The purpose of this study was to determine the feasibility of developing electronic module teaching materials (E-Modules) based on mind mapping of mutual cooperation material, for fourth grade students of SDN Mlatiharjo 2, Gajah District, Demak Regency. This type of research uses Research and Development (RnD) research using the ADDIE learning model, namely Analyze, Design, Develop, Implement, and Evaluate. The research instrument includes a validation sheet by 2 expert lecturers and class teachers, namely material expert lecturers, media expert lecturers, and a questionnaire response from educators and students. This study produces aspects of the feasibility of the content and integration of E-Modules based on mind mapping. In the assessment of material expert lecturers, it is very feasible, the presentation component of the material content of the E-Module gets a score from material expert lecturers with a percentage of 97.91% (very good). The assessment from media expert lecturers covering the graphic and attractiveness components of the E-Module gets a score with a percentage of 98.43% (very good) and is very feasible to use. The feasibility of mind mapping-based E-Module in grade IV of SDN Mlatiharjo 2 with reference to the results of teacher and student response questionnaires. This study concludes that the development of mind mapping-based E-Module on mutual cooperation material for grade IV students of SDN Mlatiharjo 2 is very feasible to be used in the learning process.